PERANAN ETIKA AKUNTAN TERHADAP PELAKSANAAN FRAUD AUDIT (Fokus Ekonomi, 2010)
Accountant as the profession to satisfy the auditing function must comply the profession’s code of ethic, and conducting the audit of the financial statement in certain way based on the ethical norm or auditing standard. Upon their professional implementation, an accountant must ensure the prescribed code of ethic to be carried. This professional code of ethic is based on the objective and consideration upon society’s trust to the quality of service given regardless of whose conducted the service. In their professional implementation, fraud auditor must obey the rule, ethic bonded them as the representation of trust upon the accounting professional. While the fraudeditor conducted all the fraud auditing stages and comply with the ethical rule, basically they show perseverance and honesty to conduct their set of audit tasks.Keywords : accountant, accounting, code of ethic, standard auditing, fraud audit.